(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. End-stage renal disease (ESRD) results in unpleasant consequences for patients, their families, and also society. Annually, each country expends a huge amount for ESRD treatment. In addition, its prevalence is dramatically growing, though it can be prevented. Many countries do not have accurate epidemiologic data about this disease. We conducted this study to measure a pooled prevalence of ESRD in the Middle East. Materials and Methods. Included articles were prospective and retrospective cross-sectional and editorial studies from January 1990 till January 2015 from the Middle East area that reported the prevalence of ESRD and renal replacement therapy. To measure pooled prevalence of ESRD we used a random effect model. For evaluating publication bias and heterogeneity, we used the Egger test and I squared test, respectively. Results. After excluding duplicates and irrelevant studies, 18 articles remained in our study. The prevalence reported in these studies varied from 55 pmp to 818 pmp. The pooled prevalence of ESRD was 360 pmp (95% confidence interval, 290 pmp to 430 pmp; I2 = 100%; P < .001). Conclusions. Most of the countries in the Middle East are categorized as developing countries. We believe that the prevalence in this region is much higher than what we measured. They lack a data registry system for most of diseases like ESRD, while it is needed for better prevention and treatment of these diseases.